Diffusion barrier layer containing sixth subgroup nitride in integrated circuit copper interconnects
By using an ultra-thin diffusion barrier layer containing the sixth sub-group nitride in the integrated circuit, the problem of failure of the diffusion barrier layer in the prior art at high temperature is solved, and the effect of maintaining excellent diffusion barrier performance at high temperature is achieved.
Patent Information
- Application Number
- CN202510102526.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The existing diffusion barrier layer fails at high temperatures, making it difficult to effectively block the diffusion of copper in integrated circuits.
An ultra-thin diffusion barrier layer containing the sixth sub-group nitride, including CrN, MoN and WN films, is prepared by magnetron sputtering technology, and process conditions such as vacuum degree, target distance, sputtering power and gas flow are controlled to ensure the high quality of the film and excellent diffusion barrier performance.
It achieves good diffusion barrier performance at high temperatures (such as 800℃, 750℃ and 700℃), extends the aging temperature of the diffusion barrier layer, and significantly improves the stability and performance of the integrated circuit.
Smart Images

Figure CN119890178A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a diffusion barrier layer containing sixth subgroup nitride in integrated circuit copper interconnection, belonging to the field of chip manufacturing. Background Art
[0002] The manufacture of chips requires multiple process steps, among which the diffusion barrier layer is a very important step. The diffusion barrier layer is usually coated with materials such as silicon nitride, aluminum nitride, refractory metals, binary compounds, ternary compounds and high entropy alloys. Its purpose is to form an oxide or nitride layer to limit the diffusion of impurities in the chip and prevent impurities from damaging the basic structure of the chip.
[0003] As the research progressed, people found that the single layer lost its integrity when the temperature exceeded 450°C, and its barrier function rapidly decayed. In order to further improve the barrier performance of the barrier layer at high temperatures, people tried TaN, Ti / TaN, W–Ti–N, Zr–B–N, AlCrTaTiZrMoN 0.2 Research and development of diffusion barriers such as TaN. For example, YM Zhou et al. studied and compared the schemes of sputtered TaN and Ti / TaN bilayer as diffusion barriers. The results showed that the sheet resistance of Cu / Ti / TaN / SiO2 / Si was lower than that of Cu / TaN / SiO2 / Si system. The Ti / TaN bilayer structure has superior diffusion isolation performance for copper, and no Cu3Si is formed before annealing to 800℃. The failure mechanism of Ti / TaN bilayer is similar to that of single-layer TaN isolation layer. After annealing at 800℃, Cu atoms diffused through the grain boundaries of Ti / TaN bilayer, and voids and ridges also appeared on the surface. Wang et al. prepared W–Ti–N diffusion barriers by reactive magnetron sputtering, characterized the surface morphology, structure and sheet resistance of Cu- / W–Ti–N / Si samples annealed at different temperatures, and discussed the failure mechanism. The results showed that the crystallization temperature of W–Ti–N amorphous film was higher than 800 °C, and the film was mainly composed of TiN and W. The prepared W–Ti–N film still had good stability at 700 °C. Meng et al. studied the thermal stability and barrier properties of Zr–B–N films deposited by reactive DC magnetron sputtering. The results showed that the deposited Zr–B–N film was amorphous, mainly composed of ZrO2 and BN and a small amount of ZrN. The amorphous Zr–B–N film had good thermal stability and barrier properties. The 5 nm Zr–B–N barrier layer could effectively block the diffusion of Cu and Si below 650 °C. The Zr–B–N film obviously recrystallized at about 650 °C, resulting in barrier failure. Summary of the invention
[0004] The present invention attempts to further improve the performance of integrated circuits by using a single-layer ultra-thin (less than or equal to 16 nm) diffusion barrier layer with simple components and simple structure.
[0005] The diffusion barrier layer containing the sixth subgroup nitride in the integrated circuit copper interconnection of the present invention comprises a diffusion barrier layer containing Cr, a diffusion barrier layer containing molybdenum nitride, and a diffusion barrier layer containing tungsten nitride. The Cr-containing diffusion barrier layer contains Cr and N.
[0006] The Cr-containing diffusion barrier layer in the integrated circuit copper interconnection of the present invention consists of Cr and N.
[0007] The diffusion barrier layer containing the sixth subgroup nitride in the integrated circuit copper interconnect of the present invention has a thickness of less than or equal to 155 nm, preferably less than or equal to 16 nm.
[0008] The diffusion barrier layer is prepared by magnetron sputtering.
[0009] When the Cr-containing diffusion barrier layer is prepared by magnetron sputtering, the following steps are controlled: The background vacuum degree is 1~10×10 -4 Pa, preferably 4~6×10 -4 Pa, more preferably 5×10 -4 Pa.
[0010] The target distance is 10 to 20 cm, preferably 14 to 18 cm, and more preferably 16 cm.
[0011] The sputtering power is 20~60W, preferably 35~45W, and more preferably 38~42W, which of course includes 40W. In the present invention, the sputtering power is relatively important to the product quality. If the sputtering power is too low, the deposition rate of the thin film will be low, but when the sputtering power is too high, target poisoning will occur. The occurrence of target poisoning will have a great impact on the deposition process. It will cause the sputtering process to be extremely unstable, the film layer to be severely damaged, the increase in internal defects may even cause damage to the surface of the target material, and greatly shorten the service life of the target material.
[0012] The working gas flow rate is 18 to 22 sccm, preferably 19 to 21 sccm, and more preferably 20 sccm.
[0013] The working pressure is 0.4 to 1.0 Pa, preferably 0.5 to 0.8 Pa, and more preferably 0.6 to 0.7 Pa.
[0014] The target material is a Cr target material with a purity greater than or equal to 99.95%.
[0015] The working gas consists of argon and nitrogen.
[0016] As a further preference, the volume ratio of argon to nitrogen in the working gas is 19:1.
[0017] As a further preference, the temperature of the substrate is 20-25°C.
[0018] The diffusion barrier layer containing Cr in the copper interconnection of the integrated circuit of the present invention can be directly attached to the copper, or attached to the liner layer, and the liner layer is attached to the copper.
[0019] In the present invention, the thickness is less than or equal to 16 nm, which exhibits excellent diffusion barrier performance. The Cr-containing diffusion barrier layer (with a thickness of about 15 nm) developed and prepared by the present invention can still maintain good diffusion barrier performance after annealing at 800°C.
[0020] When the diffusion barrier layer containing molybdenum nitride is prepared by magnetron sputtering, the following steps are controlled: The background vacuum degree is 1~10×10 -4 Pa, preferably 4~6×10 -4 Pa, more preferably 5×10 -4 Pa.
[0021] The target distance is 10 to 20 cm, preferably 14 to 18 cm, and more preferably 16 cm.
[0022] The sputtering power is 20 to 40 W, preferably 20 to 25 W, and more preferably 20 to 22 W, which of course includes 40 W.
[0023] The working gas flow rate is 18 to 22 sccm, preferably 19 to 21 sccm, and more preferably 20 sccm.
[0024] The working pressure is 0.5 to 1.0 Pa, preferably 0.5 to 0.8 Pa, and more preferably 0.6 to 0.7 Pa.
[0025] The target material is a Mo target material with a purity greater than or equal to 99.95%.
[0026] The working gas consists of argon and nitrogen.
[0027] As a further preference, the volume ratio of argon and nitrogen in the working gas is 18:2. As a further preference, the flow rate of argon in the working gas is 18 sccm and the flow rate of nitrogen is 2 sccm.
[0028] As a further preference, the temperature of the substrate is 20-25°C.
[0029] The diffusion barrier layer containing molybdenum nitride in the copper interconnection of the integrated circuit of the present invention can be directly attached to the copper or attached to the liner layer, and the liner layer is attached to the copper.
[0030] In the present invention, when the thickness of the diffusion barrier layer containing molybdenum nitride is about 15 nm, it exhibits extremely excellent diffusion barrier performance.
[0031] The diffusion barrier layer containing molybdenum nitride (with a thickness of about 15 nm) developed and prepared by the present invention can still maintain good diffusion barrier performance after annealing at 700° C.
[0032] When the diffusion barrier layer containing molybdenum nitride is prepared by magnetron sputtering, the following steps are controlled: The background vacuum degree is 1~10×10 -4 Pa, preferably 4~6×10 -4 Pa, more preferably 5×10 -4 Pa.
[0033] The target distance is 10 to 20 cm, preferably 14 to 18 cm, and more preferably 16 cm.
[0034] The sputtering power is 20 to 40 W, preferably 20 to 25 W, and more preferably 20 to 22 W, which of course includes 40 W.
[0035] The working gas flow rate is 18 to 22 sccm, preferably 19 to 21 sccm, and more preferably 20 sccm.
[0036] The working pressure is 0.5 to 1.0 Pa, preferably 0.5 to 0.8 Pa, and more preferably 0.6 to 0.7 Pa.
[0037] The target material is a W target material with a purity greater than or equal to 99.95%.
[0038] The working gas consists of argon and nitrogen.
[0039] As a further preference, the volume ratio of argon and nitrogen in the working gas is 19:1. As a further preference, the flow rate of argon in the working gas is 19 sccm and the flow rate of nitrogen is 1 sccm.
[0040] As a further preference, the temperature of the substrate is 20-25°C.
[0041] The diffusion barrier layer containing tungsten nitride in the integrated circuit copper interconnection of the present invention can be directly attached to copper or attached to a liner, and the liner is attached to copper.
[0042] In the present invention, when the thickness of the diffusion barrier layer containing tungsten nitride is about 15 nm, it exhibits extremely excellent diffusion barrier performance.
[0043] The tungsten nitride-containing diffusion barrier layer (with a thickness of about 15 nm) developed and prepared by the present invention can still maintain good diffusion barrier performance after annealing at 600°C.
[0044] When the structure of the diffusion barrier layer developed and prepared by the present invention is Cu / CrN / MN / Si, and M is Mo and / or W, even if the thickness is 15 nm, the aging temperature of the product is greater than 800°C.
[0045] Principles and advantages The thickness of the (CrN, MoN, WN) film prepared by the present invention using DC (reactive) magnetron sputtering under optimized process conditions is about 15nm. The obtained film has a smooth surface and excellent continuity. After optimization, the failure temperature of the (CrN, MoN, WN) barrier layer film is increased to 800°C, 750°C and 700°C and above, respectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a diagram showing the resistivity change of the product obtained in Example 1 after annealing at 400°C-800°C.
[0047] Figure 2 This is the GIXRD diagram of the product obtained in Example 1 after annealing at 400°C-800°C.
[0048] Figure 3 This is a SEM cross-sectional view of the product obtained in Example 1 after annealing at 400°C-800°C.
[0049] Figure 4 The resistivity change diagram of CrN film under different N2 flow rates.
[0050] Figure 5 This is a diagram showing the resistivity change of the product obtained in Example 1 after annealing at 400°C-800°C.
[0051] Figure 6 This is the GIXRD diagram of the product obtained in Example 1 after annealing at 400°C-800°C.
[0052] Figure 7 This is a SEM cross-sectional view of the product obtained in Example 1 after annealing at 400°C-800°C.
[0053] Figure 8 The resistivity change diagram of MoN film under different N2 flow rates.
[0054] Fig. 9 This is a diagram showing the resistivity change of the product obtained in Example 1 after annealing at 400°C-800°C.
[0055] Fig.10 This is the GIXRD diagram of the product obtained in Example 1 after annealing at 400°C-800°C.
[0056] Fig.11 This is a SEM cross-sectional view of the product obtained in Example 1 after annealing at 400°C-800°C.
[0057] Fig.12 The resistivity change diagram of WN film under different N2 flow rates.
[0058] Fig.13 This is the GIXRD diagram of the product obtained in Comparative Example 1 after annealing at 400°C-800°C.
[0059] Fig.14 This is the GIXRD diagram of the product obtained in Comparative Example 2 after annealing at 400°C-800°C.
[0060] Fig.15 This is the GIXRD diagram of the product obtained in Comparative Example 3 after annealing at 400°C-800°C. DETAILED DESCRIPTION
[0061] In the embodiments and comparative examples of the present invention, a Cr layer, a CrN layer, a Mo layer, a MoN layer, a W layer, a WN barrier layer thin film with a thickness of about 15 nm and a simulated Cu interconnect layer with a thickness of about 150 nm are prepared on an N-type single crystal silicon (100) substrate.
[0062] The resistivity of N-type single crystal silicon (100) substrate is 0.05-0.1Ω.CM; The purity of the target material used is greater than 99.95%, and the purity of the argon and nitrogen used is 5N grade or above.
[0063] The main equipment used are SB-5200DTD ultrasonic cleaner, TRP-450 magnetron sputtering coater and SLG1000-60 tube furnace.
[0064] Pre-treatment: First, the silicon wafer is ultrasonically cleaned in an acetone solution for 10 minutes to remove organic pollutants on the surface of the silicon wafer. After taking it out, rinse it with deionized water and blow it dry with nitrogen. Then, the silicon wafer is ultrasonically cleaned in anhydrous ethanol for 5 minutes to remove grease on the surface of the substrate to ensure that the film adheres better to the silicon substrate. After taking it out, rinse it with deionized water and blow it dry with nitrogen. Then, the silicon wafer is immersed in a 5% concentration HF solution for 2 minutes to remove the surface oxide layer. The silicon oxide (SiO2) layer on the silicon surface will hinder the deposition of the film and cause poor uniformity. After taking it out, rinse it with deionized water and blow it dry with nitrogen. Finally, it is ultrasonically cleaned in anhydrous ethanol for 5 minutes, taken out and blown dry with nitrogen for later use.
[0065] Example 1 On a spare N-type single crystal silicon (100) substrate, a chromium nitride layer is deposited by magnetron sputtering, and then a copper layer with a thickness of 150 nm is deposited to obtain a Cu (150 nm) / CrN (15 nm) / Si deposited sample; wherein the resistivity of the CrN film is 78 μΩ·cm; When depositing the chromium nitride layer, control: Background vacuum degree 5×10 -4 Pa, target distance is 16cm, sputtering power is 40W, working gas flow rate is 20sccm, working pressure is 0.6Pa. The target material used is a Cr target with a purity greater than or equal to 99.95%; the working gas used is composed of argon and nitrogen, where the flow rate of argon is 19sccm and the flow rate of nitrogen is 1sccm; The temperature of the substrate was 25°C.
[0066] When depositing the copper layer, control: Background vacuum degree 5×10 -4 Pa, target distance is 16cm, sputtering power is 60W, working gas flow rate is 20sccm, working pressure is 0.7Pa. The target material used is a Cu target with a purity greater than or equal to 99.95%; the working gas used is composed of argon gas, wherein the flow rate of argon gas is 20sccm; the temperature of the substrate is 25℃.
[0067] Then, annealing test was performed at 400℃-800℃ in nitrogen atmosphere. The resistivity change of the obtained product is shown in Figure 1 ; GIXRD patterns after annealing at different temperatures are shown in Figure 2 , SEM cross-sectional images of annealing at different temperatures are shown in Figure 3 ;Depend on Figure 2 It can be seen that the diffusion barrier aging temperature of the Cu (150 nm) / CrN (15 nm) / Si deposited sample prepared in Example 1 is about 800°C.
[0068] Example 2 Other conditions are consistent with those in Example 1, except that the flow rate of argon gas is 18 sccm, the flow rate of nitrogen gas is 2 sccm, and the resistivity of the obtained CrN film is about 105 μΩ·cm.
[0069] Example 3 Other conditions are consistent with those in Example 1, except that the flow rate of argon gas is 16 sccm, the flow rate of nitrogen gas is 4 sccm, and the resistivity of the obtained CrN film is about 140 μΩ·cm.
[0070] Based on Examples 1, 2, and 3, some explorations were done. Figure 4In order to reduce the resistivity of the CrN film, the present invention optimizes the flow rate of argon gas to 19 sccm and the flow rate of nitrogen gas to 1 sccm.
[0071] Example 4 On a spare N-type single crystal silicon (100) substrate, a molybdenum nitride layer was deposited by magnetron sputtering, and then a copper layer with a thickness of 150nm was deposited to obtain a Cu(150nm) / MoN(15nm) / Si deposited sample; the resistivity of the MoN film was 51.2μΩ·cm; When depositing the MoN layer, control: Background vacuum degree 5×10 -4 Pa, target distance is 16cm, sputtering power is 20W, working gas flow rate is 20sccm, and working pressure is 0.7Pa. The target material used is Mo target with purity greater than or equal to 99.95%; the working gas used is composed of argon and nitrogen, where the flow rate of argon is 18sccm and the flow rate of nitrogen is 2sccm; The temperature of the substrate was 25°C.
[0072] When depositing the copper layer, control: Background vacuum degree 5×10 -4 Pa, target distance is 16cm, sputtering power is 60W, working gas flow rate is 20sccm, working pressure is 0.7Pa. The target material used is a Cu target with a purity greater than or equal to 99.95%; the working gas used is composed of argon gas, wherein the flow rate of argon gas is 20sccm; the temperature of the substrate is 25℃.
[0073] Then, annealing test was performed at 400℃-800℃ in nitrogen atmosphere. The resistivity change of the obtained product is shown in Figure 5 ; GIXRD patterns after annealing at different temperatures are shown in Figure 6 , SEM cross-sectional images of annealing at different temperatures are shown in Figure 7 ;Depend on Figure 6 It can be seen that the diffusion barrier aging temperature of the Cu (150 nm) / MoN (15 nm) / Si deposited sample prepared in Example 4 is about 750°C.
[0074] Example 5 Other conditions are consistent with those in Example 4, except that the flow rate of argon gas is 19 sccm, the flow rate of nitrogen gas is 1 sccm, and the resistivity of the obtained MoN film is about 75 μΩ·cm.
[0075] Example 6 Other conditions are consistent with those in Example 4, except that the flow rate of argon gas is 16 sccm, the flow rate of nitrogen gas is 4 sccm, and the resistivity of the obtained MoN film is about 190 μΩ·cm.
[0076] Based on Examples 4, 5, and 6, some explorations were done. Figure 8 In order to reduce the resistivity of the MoN film, the present invention optimizes the flow rate of argon gas to 18 sccm and the flow rate of nitrogen gas to 2 sccm.
[0077] Example 7 On a spare N-type single crystal silicon (100) substrate, a tungsten nitride layer is deposited by magnetron sputtering, and then a 150nm thick copper layer is deposited to obtain a Cu (150nm) / WN (15nm) / Si deposited sample; wherein the resistivity of the WN film is 25μΩ·cm; When depositing the tungsten nitride layer, control: Background vacuum degree 5×10 -4 Pa, target distance is 16cm, sputtering power is 20W, working gas flow rate is 20sccm, working pressure is 0.7Pa. The target material used is W target with purity greater than or equal to 99.95%; the working gas used is composed of argon and nitrogen, where the flow rate of argon is 19sccm and the flow rate of nitrogen is 1sccm; The temperature of the substrate was 25°C.
[0078] When depositing the copper layer, control: Background vacuum degree 5×10 -4 Pa, target distance is 16cm, sputtering power is 60W, working gas flow rate is 20sccm, working pressure is 0.7Pa. The target material used is a Cu target with a purity greater than or equal to 99.95%; the working gas used is composed of argon gas, wherein the flow rate of argon gas is 20sccm; the temperature of the substrate is 25℃.
[0079] Then, annealing test was performed at 400℃-800℃ in nitrogen atmosphere. The resistivity change of the obtained product is shown in Fig. 9 ; GIXRD patterns after annealing at different temperatures are shown in Fig.10 , SEM cross-sectional images of annealing at different temperatures are shown in Fig.11 ;Depend on Fig.10 It can be seen that the diffusion barrier aging temperature of the Cu (150 nm) / WN (15 nm) / Si deposited sample prepared in Example 7 is about 750°C.
[0080] Example 8 Other conditions are consistent with those in Example 7, except that the flow rate of argon gas is 18 sccm, the flow rate of nitrogen gas is 2 sccm, and the resistivity of the obtained MoN film is about 45 μΩ·cm.
[0081] Example 9 Other conditions are consistent with those in Example 7, except that the flow rate of argon gas is 16 sccm, the flow rate of nitrogen gas is 4 sccm, and the resistivity of the obtained CrN film is about 235 μΩ·cm.
[0082] Based on Examples 7, 8, and 9, some explorations were done and the results are shown in Fig.12 In order to reduce the resistivity of the MoN film, the present invention optimizes the flow rate of argon gas to 19 sccm and the flow rate of nitrogen gas to 1 sccm.
[0083] Comparative Example 1 The other conditions are the same as those in Example 1, except that the working gas is only argon. The obtained product is: Cu (150nm) / Cr (15nm) / Si; the GIXRD patterns of the obtained product of this comparative example after annealing at different temperatures are shown in Fig.13 ;from Fig.13 It can be seen from the figure that at 750°C, the diffusion barrier layer has failed.
[0084] Comparative Example 2 The other conditions are the same as those in Example 4, except that the working gas is only argon. The obtained product is: Cu (150nm) / Mo (15nm) / Si; the GIXRD patterns of the obtained product of this comparative example after annealing at different temperatures are shown in Fig.14 ;from Fig.14 It can be seen from the figure that at 600°C, the diffusion barrier layer has failed.
[0085] Comparative Example 3 The other conditions are the same as those in Example 7, except that the working gas is only argon. The obtained product is: Cu (150nm) / W (15nm) / Si; the GIXRD patterns of the obtained product of this comparative example after annealing at different temperatures are shown in Fig.15 ;from Fig.15 It can be seen from the figure that at 600°C, the diffusion barrier layer has failed.
Claims
1. A diffusion barrier layer containing a Group VI nitride in an integrated circuit copper interconnect, characterized in that: The diffusion barrier layer includes a diffusion barrier layer containing Cr, a diffusion barrier layer containing molybdenum nitride, and a diffusion barrier layer containing tungsten nitride; The Cr-containing diffusion barrier layer contains Cr and N, preferably consists of Cr and N; The diffusion barrier layer was prepared by magnetron sputtering.
2. The diffusion barrier layer containing Group VI nitride in the integrated circuit copper interconnection according to claim 1, characterized in that: The thickness of the diffusion barrier layer is less than or equal to 16 nm.
3. The diffusion barrier layer containing Group VI nitride in the integrated circuit copper interconnection according to claim 1, characterized in that: When the Cr-containing diffusion barrier layer is prepared by magnetron sputtering, the following steps are controlled: The background vacuum degree is 1~10×10 -4 Pa, preferably 4~6×10 -4 Pa, more preferably 5×10 -4 Pa; The target distance is 10-20 cm, preferably 14-18 cm, and more preferably 16 cm; The sputtering power is 20-60 W, preferably 35-45 W, and more preferably 38-42 W; The working gas flow rate is 18-22 sccm, preferably 19-21 sccm, and more preferably 20 sccm; The working pressure is 0.4~1.0Pa, preferably 0.5~0.8Pa, and more preferably 0.6~0.7Pa; The target material is a Cr target material with a purity greater than or equal to 99.95%; The working gas is composed of argon and nitrogen; The temperature of the substrate is 20~25℃.
4. The diffusion barrier layer containing Group VI nitride in the integrated circuit copper interconnection according to claim 3, characterized in that: The volume ratio of argon to nitrogen in the working gas is 19:
1.
5. The diffusion barrier layer containing Group VI nitride in the integrated circuit copper interconnection according to claim 3, characterized in that: The diffusion barrier performance of the Cr-containing diffusion barrier layer with a thickness of 16 nm or less does not fail after annealing at 800°C.
6. The diffusion barrier layer containing Group VI nitride in the integrated circuit copper interconnection according to claim 1, characterized in that: When the diffusion barrier layer containing molybdenum nitride is prepared by magnetron sputtering, the following steps are controlled: The background vacuum degree is 1~10×10 -4 Pa, preferably 4~6×10 -4 Pa, more preferably 5×10 -4 Pa; The target distance is 10-20 cm, preferably 14-18 cm, and more preferably 16 cm; The sputtering power is 20-40 W, preferably 20-25 W, and more preferably 20-22 W; The working gas flow rate is 18-22 sccm, preferably 19-21 sccm, and more preferably 20 sccm; The working pressure is 0.5~1.0Pa, preferably 0.5~0.8Pa, and more preferably 0.6~0.7Pa; The target material is a Mo target material with a purity greater than or equal to 99.95%; The working gas is composed of argon and nitrogen; The temperature of the substrate is 20~25℃.
7. The diffusion barrier layer containing Group VI nitride in the integrated circuit copper interconnection according to claim 1, characterized in that: The volume ratio of argon and nitrogen in the working gas is 18:
2. As a further preference, the flow rate of argon in the working gas is 18 sccm and the flow rate of nitrogen is 2 sccm.
8. The diffusion barrier layer containing Group VI nitride in the integrated circuit copper interconnection according to claim 7, characterized in that: The diffusion barrier layer containing MoN with a thickness less than 16 nm does not lose its diffusion barrier performance after annealing at 700°C.
9. The diffusion barrier layer containing Group VI nitride in the integrated circuit copper interconnection according to claim 1, characterized in that: When the diffusion barrier layer containing molybdenum nitride is prepared by magnetron sputtering, the following steps are controlled: The background vacuum degree is 1~10×10 -4 Pa, preferably 4~6×10 -4 Pa, more preferably 5×10 -4 Pa; The target distance is 10-20 cm, preferably 14-18 cm, and more preferably 16 cm; The sputtering power is 20-40 W, preferably 20-25 W, more preferably 20-22 W, which of course includes 40 W; The working gas flow rate is 18-22 sccm, preferably 19-21 sccm, and more preferably 20 sccm; The working pressure is 0.5~1.0Pa, preferably 0.5~0.8Pa, and more preferably 0.6~0.7Pa; The target material is a W target material with a purity greater than or equal to 99.95%. The working gas is composed of argon and nitrogen; The temperature of the substrate is 20~25℃.
10. The diffusion barrier layer containing Group VI nitride in the integrated circuit copper interconnection according to claim 9, characterized in that: The volume ratio of argon and nitrogen in the working gas is 19:
1. As a further preference, the flow rate of argon in the working gas is 19 sccm and the flow rate of nitrogen is 1 sccm.
Citation Information
Patent Citations
Negative pole material CrN of solid film cell and its prepn
CN101066843A
Diffusion barrier layer, preparation method thereof and integrated circuit Cu interconnection structure
CN115939035A
Method for depositing metal films
EP1473761A1
Supercritical fluid-assisted deposition of materials on semiconductor substrates
US20040023453A1
Method for fabricating metal interconnection line with use of barrier metal layer formed in low temperature
US20050250314A1